The possible impact of solar activity on the summer temperature distribution over Eurasia - Lu, Wei; Xiao, Ziniu; Feng, Xueshang (Frontiers in Earth Science, 2023)
The effect of solar activity on the regional temperature in winter has been widely discussed. However, whether the summer temperature of land in the northern hemisphere is sensitive to solar activity remains to be further investigated. In this study, the empirical orthogonal function (EOF) analysis, spectrum analysis, and correlation analysis are employed to reveal the possible link between the summer temperature distribution over Eurasian land (0–180°E and 20°N−80°N) and solar activity. The results show that the corresponding time series of the second pattern significantly exhibits an 11-year solar periodicity. Its tripolar temperature distribution is similar to the correlation maps between the temperature and sunspot number (SSN). Particularly, Central Asia (50°E−90°E and 30°N−60°N) is the key response region over Eurasia. The temperature of Central Asia shows a weak but significant negative correlation with SSN. Further analysis of atmospheric circulation indicates that the solar-induced cyclonic and negative geopotential height anomalies in Central Asia weaken the high-pressure ridge on the southwest side and strengthen northwesterly winds. At the same time, with the increase in the cloud cover and the decrease of shortwave radiation, the temperature is lowered. Due to the impact of solar activity, the upper atmosphere over Eurasia forms a wave train-like structure, resulting in a tripolar temperature distribution pattern. On the other hand, the 21-year sliding correlation results suggest that the connection between solar activity and the temperature in Central Asia was strong and decadal stable until 1980. Whereas the temperature and atmospheric circulations in high latitudes become more sensitive to solar activity after 1980. Anyway, solar activity still can be considered a non-negligible factor in the prediction of the summer temperature in Eurasia.